Szempontok a keleti lelkiséghez (Keleti lelkiség?) - Cselényi István Gábor; Vallási Néprajzi Konferencia (11.) (2012) (Szeged) (2014)
Eastern spirituality reveals special features that are in many aspects different from Western spirituality. To provide a mere list, it is by no accident that Western dogmatics stem from the notion of a „single” God and mentions the Holy Trinity thereafter (De Deo uno et trino), that is, it talks about the one and tinitarian God, while the Eastern concept is fundamentally Trinitarian as it presupposes the Holy Trinity and returns to the same.Western theology talks about grace as created (gratia creata), while Eastern theology about grace as uncreated (gratia increata) and how the persons of the Holy Trinity live within us. In the West man’s ulti-mate goal is the mysterious vision or revelation (visio beatifica), while in the East it is divination (theószisz). Western theology defines the sacraments with the help of the theory of form and material, while Eastern theology emphasises the epiphany of the sacraments and also their aspect to signify the coming of the end of times. In Western view, the visibility of the Holy Eucharist is important as when on the Corpus Christi Day procession the sacraments are openly presented in the streets; in the Eastern tradition the Eucharist is hidden behind curtains on the iconostasis which reveals the connection between the Eucharist and the Church. Western theology operates with philosophical ideas, the East conjures up the events of salvation and connects us into its stream.
Keywords: Bölcsészettudományok; Filozófia, etika és vallástudományok